Solitary confinement : social death and its afterlives - Guenther, Lisa, 1971- (UPCC book collections on Project MUSE., 2013)
"Prolonged solitary confinement has become a widespread and standard practice in U.S. prisons--even though it consistently drives healthy prisoners insane, makes the mentally ill sicker, and, according to the testimony of prisoners, threatens to reduce life to a living death. In this profoundly important and original book, Lisa Guenther examines the death-in-life experience of solitary confinement in America from the early nineteenth century to today's supermax prisons. Documenting how solitary confinement undermines prisoners' sense of identity and their ability to understand the world, Guenther demonstrates the real effects of forcibly isolating a person for weeks, months, or years. Drawing on the testimony of prisoners and the work of philosophers and social activists from Edmund Husserl and Maurice Merleau-Ponty to Frantz Fanon and Angela Davis, the author defines solitary confinement as a kind of social death. It argues that isolation exposes the relational structure of being by showing what happens when that structure is abused--when prisoners are deprived of the concrete relations with others on which our existence as sense-making creatures depends. Because of this, solitary confinement is beyond a form of racial or political violence; it is also an assault on being itself. A searing and unforgettable indictment, Solitary Confinement reveals what the devastation wrought by the torture of solitary confinement tells us about what it means to be human--and why humanity is so often destroyed when we separate prisoners from all other people."--